2017
DOI: 10.1002/bapi.201710015
|View full text |Cite
|
Sign up to set email alerts
|

Der Wärmedurchgang bei Doppelfenstern – Konzept zur In‐situ‐Bewertung historischer Konstruktionen

Abstract: während bei modernen Thermofenstern, die nur eine Flügelebene aufweisen, der Gaspolster zwischen den Scheiben des Isolierglases im Zentimeterbereich liegt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Due to the fact that they have a smaller thickness (8.5 mm) compared to standard insulating glass units (minimum 14-16 mm), they can be used instead of common glass in old window units after the milling of window glass holder. The following technical issues of design and operation also require detailed study [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]: -providing thermal protection of buildings when replacing window units in historical buildings during winter operation which was caused by a change in the thermal conditions of the junction of window units to the exterior walls.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that they have a smaller thickness (8.5 mm) compared to standard insulating glass units (minimum 14-16 mm), they can be used instead of common glass in old window units after the milling of window glass holder. The following technical issues of design and operation also require detailed study [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]: -providing thermal protection of buildings when replacing window units in historical buildings during winter operation which was caused by a change in the thermal conditions of the junction of window units to the exterior walls.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that numerical models can be used to study the effects of thermal insulation on ceilings with complex cross sections [15]. Multi-sensor in situ measurements are an effective measure to test the validity of models [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Modern technological capabilities of manufacturers of translucent structures allow the mass production of window blocks with the thermal resistance of 1.0 m 2 0 С/W and higher, which exceeds the thermal resistance of external brick walls with a thickness of 770 mm (3 bricks). When they are used, the heat loss of buildings through the outer enclosure in the winter period of operation differs from traditional significantly [7][8][9][10][11][12][13][14][15]. In this case, from the point of view of providing thermal protection, the windows will not be the most vulnerable part of the outer shell of the building.…”
Section: Introductionmentioning
confidence: 99%